Dielectric Properties of Mineral Oil-based Nanofluids using Zinc Oxide Nano-composites for Power Transformer Application - Muangpratoom, P.; Kunakorn, A.; Pattanadech, N.; Vittayakorn, W.; Thungsook, K. (My University, 2018)
This research paper describes and analyzes various experiments designed to investigate the dielectric properties (at a series of pre-determined test temperatures and % moisture content) of mineral oil-based nanofluids produced by the incorporation of zinc oxide (ZnO) powder (of mean diameter less than 100nm) into a standard mineral oil, with the surfactant sorbitan mono-oleate (Span 80) added to modify the surface of the nanoparticles in all but the control sample. Five different nanofluid test samples (one control sample and four modified samples) based on the standard mineral oil were produced for testing: 1) a control sample containing no Span 80 and no ZnO, 2) a modified sample with Span 80, and ZnO volume fraction of 0.01 %, 3) a modified sample without Span 80, and ZnO volume fraction of 0.01 %, 4) a modified sample with Span 80, and ZnO volume fraction of 0.03%, and 5) a modified sample without Span 80, and ZnO volume fraction of 0.03 %. In addition, the five liquid samples above were tested to determine AC breakdown voltage at seven different temperatures in the range of 35°C to 90°C. The test circuit was set up in accordance with IEC 60156 using a sphere-sphere electrode configuration with gap spacing of 2.5 mm. Several significant results were obtained from the investigation. Firstly, ZnO nanoparticles had a positive effect on all the test solutions in which they were used. Second, a positive relationship was confirmed between breakdown voltages, temperature rise. Third, a negative correlation was established between higher concentration of ZnO nanoparticles and breakdown voltage. Fourth, the use of surfactant proved to have both positive and negative effects on breakdown voltages.
Keywords: AC breakdown voltage; mineral oil; nanofluids; temperature